2021
DOI: 10.3390/su132111705
|View full text |Cite
|
Sign up to set email alerts
|

Feedback Loops and Facilitation: Catalyzing Transformational Multi-Stakeholder Refugee Response Partnerships

Abstract: Global policies such as the recent ‘Comprehensive Refugee Response Framework’ call for a profound transformation in refugee response. To this end, collaboration with non-traditional humanitarian actors, particularly the private sector has been advocated. The application of new multi-stakeholder partnerships that transcend traditional dyadic relationships have been commended by practitioners for their ability to create stable services and markets in refugee camps. However, the adaptation of multi-stakeholder pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 106 publications
0
2
0
Order By: Relevance
“…The role of feedback loops could be essential in making sure that collaborative partners are continuously informed. A recent study (Moreno-Serna et al, 2021) on multi-stakeholder collaboration also showed that feedback loops are powerful in the consolidation of learning, and help connect the external impact of the collaboration with the internal dynamics of a partnership. The role of a facilitator remains important to promote reflection and ensure the development of relationships of trust (Moreno-Serna et al, 2021).…”
Section: Flows Of Information and Communication Related To Critical E...mentioning
confidence: 99%
See 1 more Smart Citation
“…The role of feedback loops could be essential in making sure that collaborative partners are continuously informed. A recent study (Moreno-Serna et al, 2021) on multi-stakeholder collaboration also showed that feedback loops are powerful in the consolidation of learning, and help connect the external impact of the collaboration with the internal dynamics of a partnership. The role of a facilitator remains important to promote reflection and ensure the development of relationships of trust (Moreno-Serna et al, 2021).…”
Section: Flows Of Information and Communication Related To Critical E...mentioning
confidence: 99%
“…A recent study (Moreno-Serna et al, 2021) on multi-stakeholder collaboration also showed that feedback loops are powerful in the consolidation of learning, and help connect the external impact of the collaboration with the internal dynamics of a partnership. The role of a facilitator remains important to promote reflection and ensure the development of relationships of trust (Moreno-Serna et al, 2021). In our case study, a perceived lack of feedback loops and disconnectedness from youth and activities at the local park seemed to require a close collaboration between the different stakeholders involved.…”
Section: Flows Of Information and Communication Related To Critical E...mentioning
confidence: 99%